Bioinspired Self‐Supporting Phthalocyanine@ZnIn2S4 Foam for Photocatalytic CO2 Reduction Under Visible Light Irradiation. Issue 6 (15th March 2022) - She, Ping; Qi, Yuanyuan; Bao, Tengfei; Rui, Hongbang; Guan, Buyuan; Rao, Heng; Qin, Jun-Sheng
Abstract : Molecular catalysis for photocatalytic CO2 reduction (PCR) has recently attracted much attention, whereas its scaled practical application is usually limited by the difficulty of recycling and its photochemical instability in homogeneous solutions. Immobilization of molecular catalysts on solid matrices, that is, covalent bonds or noncovalent interactions, provides a great blueprint to tackle this issue. Herein, a bioinspired self‐supporting phthalocyanine@ZnIn2 S4 (Pc@ZnIn2 S4 ) foam by growing ZnIn2 S4 nanosheets on the commercialized polyurethane foam (PF) followed by loading amino‐modified cobalt phthalocyanine (CoPc–NH2 ) is developed. The self‐supporting Pc@ZnIn2 S4 PF carrier can be directly taken out of the reaction system for the next reaction cycle without any other procedures. The optimized Pc@ZnIn2 S4 PF demonstrates superior PCR efficiency under visible light ( λ = 420 nm), achieving 474.65 μmol CO g −1 catalyst after 8 h. The superior PCR performance is attributed to the elevated light‐harvesting ability induced by the porous foam structure and the enhanced charge separation efficiency facilitated by the dimension‐matched interface between ZnIn2 S4 and Pc. The special design of the immobilization molecular catalyst on solid supporters presented herein develops an efficient strategy for solar‐driven energy conversion. Abstract : A bioinspired self‐supporting phthalocyanine@ZnIn2 S4 (Pc@ZnIn2 S4 ) foam is developed by growing ZnIn2 S4 nanosheets on a commercialized polyurethane foam (PF) followed by loading amino‐modified cobalt phthalocyanine. The self‐supporting Pc@ZnIn2 S4 PF demonstrates superior efficiency for photocatalytic CO2 reduction and can be easily taken out of the reaction system for the next reaction cycle.